Light-enhanced acid catalysis over a metal–organic framework. Issue 20 (19th February 2018) - Xu, Caiyun; Sun, Keju; Zhou, Yu-Xiao; Ma, Xiao; Jiang, Hai-Long
Abstract : A sulfonate group-functionalized metal–organic framework exhibits unprecedented light-enhanced catalytic activity, even higher than H2 SO4, and excellent recyclability toward acid-engaged reactions under light irradiation. Abstract : A Brønsted acid-functionalized metal–organic framework (MOF), MIL-101-SO3 H, was prepared for acid-engaged esterification reactions. Strikingly, for the first time, the MOF exhibits significantly light-enhanced activity and possesses excellent activity and recyclability, with even higher activity than H2 SO4 under light irradiation.